The Relationship Of Learning Motivation And Student Achievement In Online Learning In The Culinary Concertration Pkk Studi Program - Auliya, Yuni; Elida, Elida (Universitas Negeri Padang, 2022)
This research was motivated by changes in learning methods during the Covid-19 pandemic. Based on the Semester Achievement Index of students in online learning, it can be seen that there is a decrease in the percentage from the period before going online. This study aims to describe student learning motivation in online learning, describe student learning achievement in online learning, and analyze the relationship between learning motivation and student learning achievement in online learning during the Covid-19 pandemic at the PKK Study Program Concentration of Catering. This type of research is quantitative with a correlational approach. The population of this research is the students of the Culinary Concentration PKK Study Program who take online lectures totaling 383 people. The sampling technique used is proportional random sampling totaling 80 people. The data was collected by using a questionnaire via google form using a Likert scale that has been tested for validity and reliability. Data were analyzed by descriptive and correlation analysis. The results showed that overall student learning motivation was in the moderate category with a percentage of 42.2%, student achievement was in the medium category with a percentage of 36.2%, and from the results of the correlation test it could be concluded that there was no significant relationship between learning motivation and learning achievement. students in online learning during the Covid-19 pandemic at the Culinary Concentration PKK Study Program with a significance value of 0.893.